Disruption of Androgen and Estrogen Receptor Activity in Prostate Cancer by a Novel Dietary Diterpene Carnosol: Implications for Chemoprevention - Jeremy J. Johnson; Deeba N. Syed; Yewseok Suh; Chenelle R. Heren; Mohammad Saleem; Imtiaz A. Siddiqui; Hasan Mukhtar (2010)
Emerging data are suggesting that estrogens, in addition to androgens, may also be contributing to the development of prostate cancer (PCa). In view of this notion, agents that target estrogens, in addition to androgens, may be a novel approach for PCa chemoprevention and treatment. Thus, the identification and development of nontoxic dietary agents capable of disrupting androgen receptor (AR) in addition to estrogen receptor (ER) could be extremely useful in the management of PCa. Through molecular modeling, we found that carnosol, a dietary diterpene, fits within the ligand-binding domain of both AR and ER-alpha. Using a time-resolved fluorescence resonance energy transfer assay, we found that carnosol interacts with both AR and ER-alpha and additional experiments confirmed that it functions as a receptor antagonist with no agonist effects. LNCaP, 22Rv1, and MCF7 cells treated with carnosol (20-40 mumol/L) showed decreased protein expression of AR and ER-alpha. Oral administration of carnosol at 30 mg/kg 5 days weekly for 28 days to 22Rv1 PCa xenografted mice suppressed tumor growth by 36% (P = 0.028) and was associated with a decrease in serum prostate-specific antigen by 26% (P = 0.0042). These properties make carnosol unique to any known antiandrogen or antiestrogen investigated thus far for the simultaneous disruption of AR and ER-alpha. We suggest that carnosol may be developed or chemically modified through more rigorous structure-activity relationship studies for a new class of investigational agents-a dual AR/ER modulator.